2014
DOI: 10.1051/mbcb/2014025
|View full text |Cite
|
Sign up to set email alerts
|

Adénocarcinome polymorphe de bas grade : une localisation labiale

Abstract: -Polymorphous low-grade adenocarcinoma: a lip localisation. Introduction: Polymorphous low-grade adenocarcinoma (PLGA) is a carcinomatous epithelial tumour mainly located on the palate or lips. Observation: We report the case of a PLGA of the upper lip. Discussion: The low clinical specificity and histological polymorphism of PLGA make diagnosis difficult. A multidisciplinary consultation meeting of the French network of expertise on rare head and neck cancers (REFCOR and REFCORpath) allowed histological diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…As for postoperative radiotherapy, there is no established benefit, although this approach has been practiced by many authors, except for certain limited cases such as lymph node metastases, incomplete resections, and inoperable patients. [18]. Uemaetomari et al deemed postoperative radiotherapy necessary, but a large retrospective study conducted by Castle et al showed that 97% of patients did not experience recurrence approximately a decade after their surgery.…”
Section: Discussionmentioning
confidence: 99%
“…As for postoperative radiotherapy, there is no established benefit, although this approach has been practiced by many authors, except for certain limited cases such as lymph node metastases, incomplete resections, and inoperable patients. [18]. Uemaetomari et al deemed postoperative radiotherapy necessary, but a large retrospective study conducted by Castle et al showed that 97% of patients did not experience recurrence approximately a decade after their surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Il n'y a pas de bénéfice établi de la radiothérapie postopéra-toire même si ce type de thérapie a été pratiqué par de nombreux auteurs sauf pour certains cas limités incluant les métas-tases ganglionnaires, les exérèses incomplètes et les patients non opérables [20].…”
Section: Discussionunclassified